Analysis of a Tall Structure Considering Different Diaphragm Condition Using Analysis Tool ETABS : A Review - Ankit Thakre; Ankita Singhai; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2024)
In this research, the seismic analysis for 11 stories structures with reinforced concrete is executed by taking two kinds of floor diaphragms. The horizontal loads include seismic and wind loads that have been applied by using ETABS for the model of multistoried buildings along all directions for the used building, by using (ASCE 7-10 / IBC 2012) for seismic loadings and (ASCE7-5) for wind loads. According to the result data for the modeling, current study provides a great resource of information on the horizontal displacement parameters like, drift of storey, shear of storey, moments of column, axial forces and time period
Keywords: Flexible Diaphragm; Rigid Diaphragm; E-Tabs; Storey Displacement; Storey Drift; Storey Stiffness; Storey Shear